The Role of Dialogical Speech in the Formation of Foreign Language Competence in Students of Non-Linguistic Higher Education Institutions - Mirzayeva .E.T (Periodica Journal, 2023)
The article analyzes the features of teaching speech communication in a foreign language to students of a non-linguistic university of the level considering it brought examples of exercise for the formation and development of dialogic speech skills necessary for mastery of foreign language competencies.
Keywords: speech; development of communication skills; university